In Vitro and In Vivo Effects of Jia-Wei-Xiao-Yao-San in Human Breast Cancer MCF-7 Cells Treated With Tamoxifen. (May 2014) - Chen, Jiun-Liang; Chang, Chun-Ju; Wang, Jir-You; Wen, Che-Sheng; Tseng, Ling-Ming; Chang, Wen-Chi; Noomhorm, Nattanant; Liu, Hui-Ju; Chen, Wei-Shone; Chiu, Jen-Hwey; Shyr, Yi-Ming
Introduction . There is epidemiological evidence that Jia-Wei-Xiao-Yao-San (JWXYS) is the most common Chinese medicine decoction coprescribed with tamoxifen (Tam) when breast cancer is treated by hormonal therapy. However, whether there is interaction between JWXYS and Tam remains to be clarified. The aim of this study was to investigate the in vitro and in vivo effects of JWXYS on human breast cancer MCF-7 cells treated with Tam. Methods . In vitro cultured MCF-7 cells were cotreated with JWXYS and Tam. This was followed by MTT ([4, 5-cimethylthiazol-2-yl]- 2, 5-diphenyl tetrazolium bromide) assays and cell cycle analysis to assess cell proliferation; Western blot analysis was used to analyze the expression of various proteins involved in growth-related signal pathways. In addition, immunohistochemistry was used to detect autophagy among the cancer cells. In vivo analysis used female athymic nude mice implanted with MCF-7 cells; these mice were randomly assigned to 6 groups. All mice were killed humanely after 21 days of treatment; body weight, tumor volume, and tumor weight were then measured. Results . JWXYS was not cytotoxic to MCF-7 cells, based on the fact that there were no statistically significant changes between the JWXYS + Tam groups and the Tam-alone group in cell numbers, cell cycle progression, and cell proliferation signals, the latter including the expression levels of AKT, ERK, P38, p27(Kip1), and light chain (LC3)-I, II. Furthermore, using the MCF-7 xenograft mouse model, there were no significant changes between the JWXYS (1.3-3.9 gm/kg) + Tam groups and the Tam-alone group in terms of tumor weight and the protein expression levels of AKT, ERK, P38, and p27 (Kip1). However, there was a significant decrease in LC3-II protein expression with the low-dose JWXYS + Tam group but not with the middle- or high-dose JWXYS + Tam groups compared with the Tam-alone group. Conclusion . Based on in vitro studies and in vivo functional studies, there is no obvious interaction between JWXYS and Tam. However, the presence of interference at the molecular level in relation to LC3-II expression provides important information and may affect treatment strategies when physicians have patients with estrogen receptor-α(+) or progesterone receptor(+) breast cancers.